Art Pedagogics in Computer Graphics - Nebesayeva, Zhanar; Koneva, Svetlana; Tanirbergenov, Medeubek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article discusses the use of information technology, namely computer graphics. The possibility of using artpedagogicheskoy activities in computer graphics. From the perspective of the conceptual field students. Influence of processes unfolding in the information, spiritual levels, exacerbate the problem of improving the education system in accordance with the challenges of the time. In the context of the transformation of Kazakh school informatization of education is increasing scientific and practical need to find efficient models, innovative forms and methods of construction of educational pro¬tsessa. Providing favorable conditions for personal self-determination and human professio¬nalnogo. As well as substantial characteristics of the concepts of "artpedagogika" in the context of the problems solved by the visual arts. The place and importance of art in education of the younger generation.